Building the Path of Personal and Collective Transformation: the Beginning of an Action-Research Experience - Ana Lucía Chaves-Álvarez (Revista Electrónica Educare)
An action-research process is characterized by the participation of different people to find a personal and collective transformation, and by analyzing our own realities to improve them. This paper presents the experience of starting an action-research process, conducted by the author, analyzing her own everyday working practice situation.